Feedback Control Analysis for Marx’s Law of the Tendential Fall in the Rate of Profit - Park, Seong Jin; Yang, Jung Min (International Journal of Control, Automation and Systems, 2023)
This paper presents a feedback control method to analyze Marx’s law of the tendential fall in the rate of profit which is the most important Marx’s theory of capitalism. The law states that the rate of profit would tend to decline in the long run as a result of technological progress. In this paper, we set the composition of capital to be accumulated next year as a control input which is designed to increase the profit rate in the next year. Then we present certain conditions for which the control input to increase the rate of profit eventually decreases it, that is to say, the effort of capital to increase the rate of profit leads to its decrease on the contrary.
Keywords: Condition; Control inputs; Economic system; Feedback control analysis; Feedback control methods; Profit rate; S-theory; Technological progress; Economic system; feedback control; nonlinear system; profit rate